SWOT Analysis: Internal and External Factors of Saraswati Drum Corps ISI Yogyakarta - Mirrah Fitriana Maghfiroh (International Journal of Seocology, 2022)
Saraswati Drum Corps is the only marching band unit under the auspices of an art institution, that is Yogyakarta Art Institute. Even though it has participated in various events and has qualified human resource capabilities, this organization does not yet have good managerial skills. So it takes an initial step to analyze the situation in Saraswati to find strategies that can be an alternative to developing the organization. Based on the problems that arise, this study aims to determine the current internal and external conditions of the Saraswati Drum Corps. This study uses a qualitative approach to obtain results that are by the conditions in the field and the actual data. Activities were carried out to collect data in the form of reading some literature, collecting documentation, and conducting participatory observations and interviews. The results of the data obtained will be reduced to obtain SWOT analysis data consisting of strengths, weaknesses, opportunities, and threats. After obtaining data according to categories, a SWOT matrix is ​​then made. So that in this study, alternative strategies were found based on the SWOT matrix, namely SO, WO, ST, and WT strategies.